RAMP2-AS1 stabilized RAPM2 mRNA through TIA1 to inhibit the progression of non-small cell lung cancer: RAMP2-AS1 inhibited non-small cell lung cancer - Wang, Siqin; Xu, Ce; Shan, Yuanyuan; Zhang, Yi (Cellular and Molecular Biology, 2023)
As the most common subtype of lung cancer, non-small cell lung cancer (NSCLC)is responsible for a large proportion of global cancer-caused deaths. The implication of long non-coding RNAs (lncRNAs) as tumor-suppressor or carcinogenic genes in NSCLC has been widely documented. Our study sought to investigate the performance of lncRNA RAMP2 antisense RNA1 (RAMP2-AS1) in NSCLC. GEPIA bioinformatics tool and RT-qPCR were applied for assessing the expression of RAMP2-AS1 and its neighboring gene receptor activity-modifying protein 2 (RAMP2) in NSCLC. Functional assays including CCK-8 assay, colony formation assay as well as caspase-3 activity analysis and Transwell invasion assays were applied for detecting the biological phenotypes of NSCLC cells. Interaction among RAMP2-AS1, RAMP2 and T-cell intracellular antigen 1cytotoxic granule associated RNA binding protein (TIA1) was evaluated by RNA immunoprecipitation and pulldown assays. We found that RAMP2-AS1 and RAMP2 were downregulated in NSCLC. Overexpression of RAMP2-AS1 hampered proliferation and invasion, whereas induced apoptosis of NSCLC cells. Mechanistically, RAMP2-AS1 interacted with TIA1 to stabilize the mRNA of RAMP2. In conclusion, we first uncovered that RAMP2-AS1 stabilized RAPM2 mRNA through TIA1 to inhibit the progression of NSCLC, providing new insight to improve the treatment efficacy of NSCLC.